The effect of body mass index on oncological and surgical outcomes in patients undergoing radical cystectomy for bladder cancer: A multicentre study of the association of urooncology, Turkey. Issue 3 (3rd November 2020) - Izol, Volkan; Deger, Mutlu; Baltaci, Sumer; Akgul, Murat; Selvi, İsmail; Ozden, Ender; Süer, Evren; Zuhtu Tansug, Mustafa
Abstract: Objective: We aimed to evaluate the effect of body mass index (BMI) on oncological and surgical outcomes in patients who underwent radical cystectomy (RC) for bladder cancer (BC). Materials and Methods: We retrospectively assessed data from patients who underwent RC with pelvic lymphadenectomy and urinary diversion for BC recorded in the bladder cancer database of the Urooncology Association, Turkey, between 2007 and 2019. Patients were stratified into three groups according to the BMI cut‐off values recommended by the WHO; Group 1 (normal weight, <25 kg/m 2 ), Group 2 (overweight, 25.0‐29.9 kg/m 2 ) and Group 3 (obese, ≥30 kg/m 2 ). Results: In all, 494 patients were included, of them 429 (86.8%) were men and 65 (13.2%) were women. The median follow‐up was 24 months (12‐132 months). At the time of surgery, the number of patients in groups 1, 2 and 3 were 202 (40.9%), 215 (43.5%) and 77 (15.6%), respectively. The mean operation time and time to postoperative oral feeding were longer and major complications were statistically higher in Group 3 compared to Groups 1 and 2 ( P  = .019, P  < .001 and P  = .025, respectively). Although the mean overall survival (OS), cancer‐specific survival (CSS), recurrence‐free survival (RFS) and metastasis‐free survival (MFS) was shorter in cases with BMI ≥ 30 kg/m 2 compared with other BMI groups, differences were not statistically significant ( P  = .532, P  = .309, P  = .751 and P  = .213, respectively). Conclusion: Our study showed that although major complications are more common in obese patients, the increase in BMI does not reveal a significant negative effect on OS, CSS, RFS and MFS.